Efendigil Family’s Poems About Cataract Disease - Karataş, Ahmet (Fırat University, 2019)
Mufti Ömer Naîmî Efendi, one of the most important members of the Efendigil family, whose fame reached all of Anatolia thanks to his muftis and mudarrisas, and his grandson Mudarris and Mufti of Mamuratulaziz (Elazığ) Mehmed Kemaleddin have suffer from cataract. Ömer Naîmî Efendi did not get positive results from the treatments and had to live blindly for the rest of his life. But Kemaleddin Efendi came to Istanbul and cured Esad Pasha, the famous eye specialist of the time, and he recovered his health. He was accompanied by his son Ömer Naîmî, who would later lose his eye because of diabetes. Ömer Naîmî (grandfather), Kemaleddin (grandson) and Ömer Naîmî (grandson’s son) explained the difficulties they experienced due to illness in poems. On the other hand, besides being a doctor, one of the leading statesmen of his era, Esad Pasha is a person who has poetry and music taste and sometimes writes poetry. The cataract adventure was the main factor that brought together three poets, the patient, the companion and the doctor in the same center. In this article, the interest of doctor Esad Pasha in poetry is examined and the poems written by Efendigil family due to cataracts are determined and transferred to today’s letters and evaluated.

Yetiştirdiği müderris ve müftüleri sayesinde şöhreti bütün Anadolu’ya ulaşan Harputlu (Ma?mûretü’l-azîz/ El?aziz/ Elazığ) İmâmzâde/Efendigil âilesinin en mühim fertlerinden olan Kasîde-i Bürde şârihi diye ünlenmiş Harput müftüsü Ömer Naîmî Efendi ve torunu müderris, Ma?mûretü’l-azîz müftüsü Mehmed Kemâleddin Efendi katarakt hastalığına yakalanmışlar, bu süreçte çok sıkıntı çekmişlerdir. Ömer Naîmî Efendi tedâvilerden müsbet netice alamamış, ömrünün geri kalanını a?mâ bir şekilde sürdürmek zorunda kalmıştır. Kemâleddin Efendi ise İstanbul’a gelerek devrin meşhur göz mütehassısı Esad Paşa’ya tedâvi olmuş ve sağlığına kavuşmuştur. İstanbul yolculuğunda ona bilâhere kendisi de diyabet yüzünden bir gözünü kaybedecek olan büyük oğlu Ömer Naîmî Bey refâkat etmiştir. Dede Ömer Naîmî ile Kemâleddin Efendiler hastalık sebebiyle yaşadıkları zorlukları, Ömer Naîmî Bey de babasına refâkat sırasında yaşadıklarını şiirle dile getirmişlerdir. Öte yandan doktorluğu yanında devrinin önde gelen devlet adamlarından da biri olan Esad Paşa şiir ve musiki zevkine sahip, şâirlik iddiası gütmemesine rağmen ara sıra şiir yazan bir şahsiyettir. Katarakt macerâsı üç şâiri, hastayı, refakatçiyi ve doktoru aynı merkezde buluşturan esas âmil olmuştur. Bu makalede Doktor Esad Paşa’nın şiirle ünsiyeti ele alınmış, Efendigil âilesinin katarakt sebebiyle yazdığı şiirler Şark İstiklâl Mahkemesi Arşivi’ndeki defterlerden tespit edilerek bugünkü harflere aktarılıp değerlendirilmiştir.
HARPUTLU EFENDİGİL ÂİLESİNİN YAKALANDIKLARI KATARAKT HASTALIĞIYLA İLGİLİ MANZUMELERİ